Interdisciplinaridade nas possibilidades de leitura de Abril Despedaçado - Magno, Maria Ignês Carlos (Comunicação & Educação, 2005)
The motion picture Abril Despedaçado, by Walter Salles, is pedagogic support to a rich, creative and comprehensive interdisciplinary work. From the dialogue with literature – the film is an adaptation of an Albanese novel – and poetry, its music and photography are elements that stand an interdisciplinary work in classroom with the interface set between cinema and art. But the possibility of other interpretations is not restricted to that field. It is enlarged by the historical, geographic, cultural and social analyses allowed by the film. The author also recovers the possibility of the exercise in the field of language: the word and its absence define the codes and dialogues about life and death, the word is used as a resource to arouse imaginary and return to the narrative route, recreate fate. Word-poetry converted into images that avoid words because they have another sort of writing: the photographic writing, the cinematographic writing permeated by a musical writing. What is important in this exercise is the openness to the dialogue with the cinematographic work and the significances that it suggests.